A clinicopathological study of cutaneous lichen planus - Asmita Parihar; Sonal Sharma; Sambit Nath Bhattacharya; Usha Rani Singh (Wolters Kluwer Medknow Publications, 2015)
Background: Lichen planus is an idiopathic subacute or chronic inflammatory disease of the skin, mucous membranes and nails. We studied the clinicopathological profile of lichen planus in Indian population. Methods: A total of 145 cases of histologically diagnosed lichen planus samples were included. Clinical features like age, sex, type of lichen planus, location were recorded in the case record form. Histological features of lichen planus were studied. Results: Out of 145 cases, majority (61%) were of classical lichen planus. Majority of cases were in the age group of 20-40 years and showed female preponderance. Most commonly, violaceous lesions occurred in lichen planus, pigmented in lichen planus pigmentosus, and both violaceous and pigmented in lichen planopilaris. Conclusions: In Indian population, common age of occurrence of lichen planus is lower as compared to western literature, and a large number of cases (28%) are in the paediatric age group (<18 years).